2010
DOI: 10.1007/s11706-010-0084-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and mechanical properties of ZrB2-based ceramics using MoSi2 as sintering aids

Abstract: ZrB 2 (zirconium diboride)-based ceramics reinforced by 15vol.% SiC whiskers with high density were successfully prepared using MoSi 2 as sintering aids. The effects of sintering condition and MoSi 2 content on densification behavior, phase composition, and mechanical properties of SiC w /ZrB 2 composites were studied. Nearly, fully dense materials (relative density > 99%) were obtained by hot-pressing (HP) at 1700°C-1800°C in flow argon atmosphere. The grain size of ZrB 2 phase in the samples sintered by HP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The collected load versus time plot were used to generate the biaxial stress versus time plot shown in Figure 10 where the load was converted into stress using Equation 1. The biaxial strength measured at room temperature for three samples tested was equal to 225.31, 257.90, and 329.85 MPa, which is rather below of the reported uniaxial bending strength of ZrB 2 based ceramic composites, such as 674 ± 130 MPa of 4-point bending strength of ZrB 2 -SiC [19] measured at room temperature or 564.72 ± 11.21 MPa of 3-point bending strength of ZrB 2 -15vol.-%SiC-15vol.-%MoSi 2 [20]. While it is not possible to directly correlate the biaxial strength with the strength values obtained by 4- or 3-point bending techniques, it is still understood that the biaxial strength of ZrB 2 -30wt-%SiB 6 ceramic composite is rather low likely because of the decomposition of SiB 6 into different phases during sintering.…”
Section: Design and Development Of The Ring-on-ring Jigmentioning
confidence: 85%
See 1 more Smart Citation
“…The collected load versus time plot were used to generate the biaxial stress versus time plot shown in Figure 10 where the load was converted into stress using Equation 1. The biaxial strength measured at room temperature for three samples tested was equal to 225.31, 257.90, and 329.85 MPa, which is rather below of the reported uniaxial bending strength of ZrB 2 based ceramic composites, such as 674 ± 130 MPa of 4-point bending strength of ZrB 2 -SiC [19] measured at room temperature or 564.72 ± 11.21 MPa of 3-point bending strength of ZrB 2 -15vol.-%SiC-15vol.-%MoSi 2 [20]. While it is not possible to directly correlate the biaxial strength with the strength values obtained by 4- or 3-point bending techniques, it is still understood that the biaxial strength of ZrB 2 -30wt-%SiB 6 ceramic composite is rather low likely because of the decomposition of SiB 6 into different phases during sintering.…”
Section: Design and Development Of The Ring-on-ring Jigmentioning
confidence: 85%
“…The collected load versus time plot were used to generate the biaxial stress versus time plot shown in Figure 10 where the load was converted into stress using Equation 1. The biaxial strength measured at room temperature for three [20]. While it is not possible to directly correlate the biaxial strength with the strength values obtained by 4-or 3-point bending techniques, it is still understood that the biaxial strength of ZrB 2 -30wt-%SiB 6 ceramic composite is rather low likely because of the decomposition of SiB 6 into different phases during sintering.…”
Section: Biaxial Strengthmentioning
confidence: 99%
“…In another work, Mashhadi et al [18] Moreover, numerous authors have been investigated the influences of whiskers silicon carbide (SiCw) on the mechanical properties of ZrB2 composites [32][33][34]. Furthermore, Li et al [35] determined the fracture toughness of the highly-dense ZrB2 -15 vol.% SiCw (whiskers) -MoSi2 composites through the single-edged notch beam (SENB) mode. They concluded that the fracture toughness of the ceramics improved with increasing MoSi2 concentration and rising the sintering temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of silicides such as TiSi 2 , ZrSi 2 , CrSi 2 and TaSi 2 improved the densification of ZrB 2 by formation of liquid phases during sintering. [21][22][23]. Metallic addition such as Ni is also reported to improve the densification by liquid phase sintering [19].Though, metal and silicide additions lower the hot pressing temperature, they are also expected to deteriorate the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%